Health problems and healthcare service utilisation amongst homeless adults in Africa- a scoping review - Benedict Osei Asibey; Elizabeth Conroy; Brahmaputra Marjadi (BMC, 2020)
Abstract Background Homelessness is a growing concern as it affects a large number of people worldwide. Individuals and families experiencing homelessness are vulnerable in terms of health and underutilise health services. Despite being a global problem, not much is known about the range and breath of literature exploring health problems and health care service utilisation among homeless adults in Africa. Objectives To identify the nature and scope of existing evidence on physical and mental health, and health service utilisation among homeless adults in Africa. The review aimed to examine how research is conducted, identify gaps, guide future research, and make recommendations for development and implementation of policies and practices. Methods A search of articles and reports involving six databases: Scopus, MEDLINE, CINAHL, PubMed, African Journal Online, and Google Scholar was conducted from June 2018 to February 2019. Studies published between 1980 and 2019 that examined the health problems and health service utilisation among homeless adults in Africa were considered. Manual search in reference lists and grey literature was also done to add reports. Data was extracted manually using a charting developed. A descriptive analysis and narrative synthesis were performed. Results Of 761 records found, 14 satisfied the pre-determined inclusion and exclusion criteria. Three themes emerged from the studies: Physical health problems, mental health problems; and healthcare services utilisation. Of the 14 included studies, nine studied and reported physical health problems such as sexually transmitted infections, injuries and disabilities, respiratory and cardiac diseases. Five studies explored mental health problems such as psychotic disorders, mood disorders, self-harm and suicidal behaviour. Only five studies investigated utilisation of different types of health care services among homeless people. Conclusions Evidence shows that homeless adults suffered from a range of physical and mental health problems, and underutilisation of health care services. However, there is lack of information on the complex interrelationship between homelessness and health, as well as differences in prevalence of health problems among the various sub-groups of homeless. There is also lack of information regarding utilisation other important healthcare services such as mental health services, alcohol and drugs services, and accident and emergency service, and future researches should address that. Also, attention should be given to intervention models for complex and effective physical and psychiatric care as well as social support to address the homeless people's health vulnerabilities.